Cover Feature: Refinement of Crystal Structure and its Application for Catalytic Materials (Eur. J. Inorg. Chem. 21/2025) - da Silva, Gabriel Ribeiro [UNESP]; da Silva, Gabriel Alves [UNESP]; Querino, João Pedro Dias [UNESP]; Possato, Luiz Gustavo [UNESP] (Wiley, 2025)
The Cover Feature presents a vibrant cyclic flowchart illustrating the catalytic research workflow. It begins with X‐ray diffraction (XRD) data, followed by Rietveld refinement and extraction of structural parameters. These insights guide catalyst design/modification, which is then tested in catalytic reactions, culminating in catalytic activity results, thus completing the research cycle. More information can be found in the Review by L. G. Possato and co‐workers (DOI: 10.1002/ejic.202500051).